Consumer Attitude Formation Toward Brands Through Virtual Influencer Product Placement: Evidence from an Experimental Study - Nur Wahyudi; Moh. Fauzi; Nur Fitriyani (CV. Jala Berkat Abadi, 2026)
This study aims to analyze the influence of product placement through virtual influencers on the formation of consumer attitudes, including attitudes toward the influencer, attitudes toward the product placement, and attitudes toward the brand. The research employed a post-test experimental design without a control group, involving 279 respondents. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results indicate that attitudes toward virtual influencers and product placement significantly contribute to the formation of positive brand attitudes, particularly when the content is delivered credibly and aligns with the audience’s values. This study contributes to the understanding of the effectiveness of product placement in shaping consumer attitudes.